The Problem of Customary Marriage and the Solution of Temporary Marriage - Seyyed Abolhasan Navvab (Religious Inquiries, 2020)
Customary marriage (nikāḥ ‘urfī)—non-official married life of a couple—is a new phenomenon increasingly spreading throughout the Arab world. Legal and social consequences of customary marriage have led many socio-jurisprudential scholars to forbid all its varieties. The strategy has, nevertheless, failed to restrain the spread of this type of marriage. In this paper, I argue that one fundamental religiously acceptable solution is temporary marriage. Although Muslims have disagreed over the legitimacy of temporary marriage, I argue that they all agree over its original legitimacy according to the Quran and Hadith, and then I show that there is no decisive evidence for the subsequent abrogation of its legitimacy. Moreover, I argue that temporary marriage can serve the purposes of customary marriage. Thus, all Muslims can accept temporary marriage as a religious replacement for customary marriage.